Desenvolvimento científico e tecnológico no Estado de São Paulo: uma análise de casos múltiplos - Zaparolli, Nathália Gonçalves (Universidade Federal de São Carlos, 2022)
This thesis understands how the local elites associate, articulate themselves with regard to the development of science, technology and innovation policies, related to the local economic development, specifically the implementations of the Technology Parks in the São Paulo’s interior. The state of São Paulo was chosen because it is the first to install a Technological Park in Brazil and has specific laws for this enterprise, in addition to being the state that most invests in science, technology and innovation. The interior of the state, due to the fact that it has little systematized information about these types of developments and about the elites active in this type of policy. In addition to the search for decentralization of policies around the 1990s. As the Technological Park is one of these policies, it involves the proposal of local development, together with the relations between State-universities-companies, linked to the proposal of science and technology and research and development. A bibliographic survey on neoliberalism, science, technology and innovation policies, local development and elites will be carried out. Analysis of government perception of policies related to Technology Parks. Mapping of the agents involved (individuals and private and public institutions). Construction of fields and capitals, as well as the habitus of these elites.
Scientific and technological development in the State of São Paulo: a multiple case analysis
Keywords: Política de Ciência, Tecnologia e Inovação; Desenvolvimento econômico; Desenvolvimento científico e tecnológico; Casos múltiplos; Elites científicas; Parques tecnológicos; Technological Parks; Science, Technology and Innovation Policy; Economic Development; Scientific and Technological Development; Scientific Elites; Multiple Cases; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS; CIENCIAS HUMANAS::CIENCIA POLITICA; CIENCIAS HUMANAS